2018
DOI: 10.7554/elife.36607
|View full text |Cite
|
Sign up to set email alerts
|

Revealing a novel nociceptive network that links the subthalamic nucleus to pain processing

Abstract: Pain is a prevalent symptom of Parkinson’s disease, and is effectively treated by deep brain stimulation of the subthalamic nucleus (STN). However, the link between pain and the STN remains unclear. In the present work, using in vivo electrophysiology in rats, we report that STN neurons exhibit complex tonic and phasic responses to noxious stimuli. We also show that nociception is altered following lesions of the STN, and characterize the role of the superior colliculus and the parabrachial nucleus in the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 82 publications
6
48
0
Order By: Relevance
“…Although recent evidences revealed the role of STN in neuronal pain processing, 21 the resistance to 94 the foot-shock induced by the STN 8 Hz stimulation did not reflect changes in pain perception, since 95 such treatment (6 h/day, 14 days) of 'shock-sensitive' animals did not affect nociceptive responses on 96 a hot-plate (Extended data Fig. 5).…”
mentioning
confidence: 90%
“…Although recent evidences revealed the role of STN in neuronal pain processing, 21 the resistance to 94 the foot-shock induced by the STN 8 Hz stimulation did not reflect changes in pain perception, since 95 such treatment (6 h/day, 14 days) of 'shock-sensitive' animals did not affect nociceptive responses on 96 a hot-plate (Extended data Fig. 5).…”
mentioning
confidence: 90%
“…Considering that STN neurons respond to nociceptive stimuli (27,35), and that STN DBS effectively relieves pain symptoms in some PD patients (28,30,32), we wondered whether the hyperactivity in STN neurons contributes to pain hypersensitivity in parkinsonian mice. To investigate this, we injected adenoassociated virus (AAV)-CaMKII-NpHR3.0-eYFP into the STN (Fig.…”
Section: Unilateral Lesion Of Snc Da Neurons Leads To Mechanical and mentioning
confidence: 99%
“…Although abnormal activity in the STN plays a critical role in parkinsonian motor deficits (16,26), its association with pain symptoms in PD has not been well studied. An in vivo electrophysiological study revealed that STN neurons have faster spontaneous firing and stronger responses to nociceptive stimuli in parkinsonian rats compared with control rats (27). Deep brain stimulation (DBS) in patients with PD effectively relieves musculoskeletal and dystonic pain, but not central or neuropathic pain (28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…3A). Interestingly, these areas are known to either relay aversive sensory signals or integrate sensory information with emotional valence [19][20][21][22] . We also investigated downstream brain areas that receive direct input from the PBL Oprm1 neurons by stereotaxic injection of recombinant AAV that express ChR2:eYFP in a Cre-dependent manner (AAV-DIO-ChR2:eYFP), which is expressed in the cell body and axon terminals ( Fig.…”
Section: Input/output Pathways Of Pbl Oprm1 Neuronsmentioning
confidence: 99%